2019
DOI: 10.17219/acem/110320
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception of smile attractiveness as a reliable predictor of increased patient compliance with an orthodontist

Abstract: Background. Predicting the cooperation of orthodontic patients seems to be of the utmost importance for successful results in treatment with removable appliances, especially if their cost is to be covered from public funding. Therefore, the issue of unbiased pre-treatment assessment of cooperation still calls for an investigation. Objectives. The objective of this study was to check whether smile attractiveness and its importance, subjectively evaluated by the patients/their caregivers, are reliable predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…The overall assessment of facial aesthetics is very complex and must take into account numerous and different factors that can affect facial and dental aesthetics that can be related both to hard and soft tissues [36][37][38]; moreover, the use of 3D low dose CT investigation allows for an extremely more accurate evaluation of the anatomical structures of the facial mass and therefore to carry out a therapeutic program that takes into account the aesthetic effects of a corrective treatment of the dento-skeletal structures [39,40]. The results of our research once again highlight the importance of dental aesthetics in the lives of adolescents and young adults, with particular reference to the female gender, emphasizing the relevance of psychological parameters in orthodontic research and clinical practice, in line with well-known literature items [41][42][43].…”
Section: Discussionsupporting
confidence: 66%
“…The overall assessment of facial aesthetics is very complex and must take into account numerous and different factors that can affect facial and dental aesthetics that can be related both to hard and soft tissues [36][37][38]; moreover, the use of 3D low dose CT investigation allows for an extremely more accurate evaluation of the anatomical structures of the facial mass and therefore to carry out a therapeutic program that takes into account the aesthetic effects of a corrective treatment of the dento-skeletal structures [39,40]. The results of our research once again highlight the importance of dental aesthetics in the lives of adolescents and young adults, with particular reference to the female gender, emphasizing the relevance of psychological parameters in orthodontic research and clinical practice, in line with well-known literature items [41][42][43].…”
Section: Discussionsupporting
confidence: 66%
“…In other words, the patients' acceptance remained stable during rst 5 months of treatment. This nding not only is in agreement with the results of Sergl et al [23] who found no signi cant change in the frequency of patient complaints regarding orthodontic appliance after 6-month assessment period; it is also the evidence-based ampli cation of research by Sarul et al, who proved that a patient's low evaluation of their smile is a reliable predictor of cooperation, prior to treatment beginning [24]. Altogether, it allows summing up that use of psychological tests for prediction of a patient's compliance can be helpful for clinicians hesitating, whether to start an early treatment of malocclusion or to postpone the therapy until camou age or orthognathic protocols may be introduced.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in agreement with the results of Sergl et al [23] who found no significant change in the frequency of patient complaints regarding orthodontic appliance after 6-month assessment period. Moreover, this result is the evidence-based strengthening point for the research by Sarul et al, who proved that a patient's low evaluation of their smile is a reliable predictor of cooperation, before the beginning of the treatment [24]. Altogether, it allows summing up that use of psychological tests for prediction of a patient's compliance can be helpful for clinicians who are uncertain whether to start removable orthodontic treatment of malocclusion or to postpone the therapy until camouflage or orthognathic protocols are introduced.…”
Section: Discussionmentioning
confidence: 60%